Filling streamflow data gaps through the construction of rating curves in the Lake Tana Sub-basin, Nile Basin - Haile, Alemseged Tamiru; Geremew, Y.; Wassie, S.; Fekadu, A. G.; Taye, Meron Teferi (IWA Publishing, 2023)
In recent decades, streamflow data remain inaccessible for most river gauges in Ethiopia due to a lack of updated stage–discharge relationships, also called rating curves. In this study, researchers and hydrologic technicians collaborated to fill the recent streamflow data gaps at three gauging stations in the Lake Tana sub-basin of the Nile River. We conducted extensive field campaigns to improve the coverage of stage–discharge measurements for rating curve development. We evaluated the rating curve uncertainty during the time of its establishment and the sensitivity of the rating curves to sample size. The stage–discharge measurements conducted by the hydrological agency during the period 2016–2020 were found inadequate in number and coverage to establish reliable rating curves. Hence, converting recent water level measurements to discharge data was made possible using the rating curves developed in this study. The converted discharge data will be accessible to researchers to investigate the sub-basin’s hydrology. Our study emphasizes the need to improve the stage–discharge measurement frequency to keep up with the frequent change in the morphology of the rivers’ channels. The study demonstrated that collaboration between the data provider and data users can improve streamflow data availability and accessibility, which has become an increasing global challenge.